The chain-mediating roles of social support and depression in the relationship between tuberculosis knowledge and self-management: a cross-sectional study based on the ABC-X model - Gu, Chune; Liu, Bofei; Wang, Huijuan; Ma, Yaling; Guo, Lei (Frontiers in Public Health, 2025)
Background and objectiveSelf-management plays a vital role in tuberculosis (TB) care, yet remains suboptimal among patients due to limited disease knowledge and psychosocial challenges. While prior studies have explored the individual roles of knowledge, social support, or depression in TB treatment, few have examined their interactive and sequential effects. This study aimed to investigate whether perceived social support and depression mediate the relationship between TB knowledge and self-management, using the ABC-X family stress model as the theoretical framework.MethodsA cross-sectional survey was conducted. Using convenience sampling to select 204 patients with primary pulmonary TB hospitalized at a tertiary TB hospital in Ningxia, China. Participants completed validated questionnaires assessing TB knowledge, perceived social support, depression, and self-management ability. Correlation analysis was used to assess associations among key variables. Mediation analysis was performed using SPSS PROCESS macro (Model 6), with 5,000 bootstrap resamples to estimate direct and indirect effects.ResultsTB knowledge was positively correlated with self-management and perceived social support, and negatively correlated with depression. Perceived social support was negatively correlated with depression and positively correlated with self-management. Depression was negatively correlated with self-management. The chain-mediating path—TB knowledge → social support → depression → self-management—was statistically significant and accounted for 5.00% of the total effect, while the total indirect effect explained 42.74% of the total effect.ConclusionThis study demonstrated that TB knowledge significantly influences self-management, both directly and indirectly, through the sequential mediating roles of perceived social support and depression. Enhancing TB knowledge alone may be insufficient without concurrently addressing social support and mental health. Multidimensional interventions integrating education, social support enhancement, and psychological care are essential for improving patient adherence and outcomes. The ABC-X model provides a useful framework for guiding future TB self-management interventions.